Efficient photochemical water oxidation by a dinuclear molecular ruthenium complex. Issue 10 (19th December 2014) - Laine, Tanja M.; Kärkäs, Markus D.; Liao, Rong-Zhen; Åkermark, Torbjörn; Lee, Bao-Lin; Karlsson, Erik A.; Siegbahn, Per E. M.; Åkermark, Björn
Abstract : A dinuclear Ru complex housing an anionic ligand scaffold has been developed. The designed Ru complex was found to efficiently mediate the photochemical oxidation of H2 O when using [Ru(bpy)3 ] 2+ -type photosensitizers. Abstract : Herein is described the preparation of a dinuclear molecular Ru catalyst for H2 O oxidation. The prepared catalyst mediates the photochemical oxidation of H2 O with an efficiency comparable to state-of-the-art catalysts.